Multistage Gold Mineralization at The Wanagon Gold Prospect, Ertsberg District, Mimika Regency, Papua Province, Indonesia - Endang Hartiningsih; Syafrizal Syafrizal; IGB Eddy Sucipta; Sudarto Notosiswoyo (Geological Agency, 2022)
DOI:10.17014/ijog.9.3.279-290The Wanagon Gold prospect area located in the Ertsberg District, Papua Province, the eastern part of Indonesia, is predominantly underlain by Upper Mesozoic to Cenozoic sedimentary rocks intruded by the Wanagon Sill monzodiorite-diorite and andesite intrusion (Wanagon Dike). The study by previous researchers at Wanagon Gold prospect was based on pre-2005 exploration data and did not contain extensive additional drillings in 2007-2011. This paper aims to elucidate the genesis of the Wanagon Gold deposits based on the latest exploration data. The mineralogy was determined by using thin section and polish section analyses, a scanning electron microscope with an energy dispersive spectrometer (SEM-EDS), X-ray diffraction (XRD), and Near-Infrared spectroscopy (NIR). The chemical composition of the rock was identified using an X-ray fluorescence spectrometer (XRF). Gold mineralization is associated with pyrite, of which there are three types of gold-bearing pyrite: (1) massive pyrite, (2) disseminated pyrite, and (3) fine-grained pyrite associated with clay minerals. Only massive pyrite contains visible gold-bearing minerals such as native gold, electrum, and gold-telluride minerals, while in nonmassive pyrite, gold is only detected by the assay. The deposit is interpreted as structurally controlled distal gold skarn. Instead, its local association of gold with arsenic also indicates a minor component of more-distal sediment-hosted type gold mineralization.